The New Consensus from a Traditional Keynesian and Post-Keynesian Perspective: A worthwhile foundation for research or just a waste of time? - Sebastian Dullien (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
This paper examines in how far the DSGE model which is often dubbed the New Keynesian Consensus is compatibel with a Post-Keynesian or traditional Keynesian understanding of the economy. It is argued that while at first sight DSGE models seem to include a lot of traditional Keynesian or even Post-Keynesian elements such as endogeneous money or the need for an active central bank, the mechanisms at work are completely incompatible with a traditional or Post-Keynesian understanding of the working of the macroeconomy.
urn:nbn:de:101:1-201101312773
Keywords: E00; E10; 330; DSGE; New Keynesian Consensus; Monetary Policy; Fiscal Policy; endogenous money